Anticipatory Motor Planning and Control of Grasp in Children with Unilateral Spastic Cerebral Palsy - Jennifer Gutterman; Trevor Lee-Miller; Kathleen M. Friel; Katherine Dimitropoulou; Andrew M. Gordon (Brain Sciences, 2021)
Children with unilateral spastic cerebral palsy (USCP) have impairments in motor planning, impacting their ability to grasp objects. We examined the planning of digit position and force and the flexibility of the motor system in covarying these during object manipulation. Eleven children with a left hemisphere lesion (LHL), nine children with a right hemisphere lesion (RHL) and nine typically developing children (controls) participated in the study. Participants were instructed to use a precision grip with their dominant/less affected hand to lift and keep an object level, with either a left, centered or right center of mass (COM) location. Digit positions, forces, compensatory torque and object roll where measured. Although children with USCP generated a compensatory torque and modulated digit placement by lift-off, their index finger was either collinear or higher than the thumb, regardless of COM location, leading to larger rolls after lift-off especially for the RHL group. The findings suggest that while the kinetics of grasp control is intact, the kinematics of grasp control is impaired. This study adds to the understanding of the underlying mechanisms of anticipatory planning and control of grasp in children with USCP and may provide insights on how to improve hand function in children with USCP.